2002
DOI: 10.1103/physrevb.66.085203
|View full text |Cite
|
Sign up to set email alerts
|

Photoluminescence fromZnS1xTexalloys under hydrostatic pressure

Abstract: ZnS 1Ϫx Te x (0.02рxр0.3) alloys are studied by photoluminescence under hydrostatic pressure at room temperature. Only a wide emission band is observed for each sample. Its peak energy is much lower than the corresponding band gap of alloys. These bands are ascribed to the radiative annihilation of excitons bound at Te n (nу2) isoelectronic centers. The pressure coefficients of the emission bands are smaller than those of alloy band gaps from 48% to 7%. The difference of the pressure coefficient of the emissio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 22 publications
(33 reference statements)
2
3
0
Order By: Relevance
“…This is expected as we discussed before that the impurity states consist almost entirely of the host valence-band states. For the single Te impurity, our calculated pressure coefficient is still close to the host material, but the experimental results of Fang et al 31,32 have a pressure coefficient of 89 meV/GPa. This could be just an anomaly of the single sample measured in Ref.…”
Section: F Impurity State Pressure Coefficientsupporting
confidence: 74%
See 1 more Smart Citation
“…This is expected as we discussed before that the impurity states consist almost entirely of the host valence-band states. For the single Te impurity, our calculated pressure coefficient is still close to the host material, but the experimental results of Fang et al 31,32 have a pressure coefficient of 89 meV/GPa. This could be just an anomaly of the single sample measured in Ref.…”
Section: F Impurity State Pressure Coefficientsupporting
confidence: 74%
“…However, for the Te n (nу2) clusters, their pressure coefficients are similar to that of bulk ZnS. 31 It is not clear what causes the large pressure coefficient for Te 1 . It is not even sure whether that is only an anomaly in the measured samples.…”
Section: Introductionmentioning
confidence: 99%
“…From their graph, the pressure coefficient is almost constant with respect to composition. We calculate for this material at x = 0.3 and find the value to be 5.732 meV/kbar which is very close to the value of Fang et al [21] within experimental uncertainty. Moreover, the band gap pressure coefficient for GaAs 0.88 Sb 0.12 is reported by Prins et al [22] to be 9.5 meV/kbar and our calculations show value of 11.516 meV/kbar, close to that of GaAs.…”
Section: Comparison With Experiments and Other Calculationssupporting
confidence: 70%
“…From the perspective of the above analyzed trends with respect to nearest neighbor distance and ionicity in the order of CdZnS, CdZnSe, CdZnTe, our result is also reasonable. For ternary compound ZnS 0.3 Te 0.7 , Fang et al [21] found that the band gap pressure coefficient is about 6.2 meV/kbar. From their graph, the pressure coefficient is almost constant with respect to composition.…”
Section: Comparison With Experiments and Other Calculationsmentioning
confidence: 98%
“…It was observed that the binding energy decreases monotonically with an increase in the composition of Te. Further, the potential differences between the Te n clusters and the host atoms decreases with an increase in the Te composition [39]. The spectra of samples with a Te concentration of less than 1% show two emission bands from the Te 1 and Te 2 centers.…”
Section: Optical Characteristics Of Zns and Zns:te Nwsmentioning
confidence: 93%